2020
DOI: 10.29252/jhc.22.1.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antenatal Physiological Classes on Depression, Anxiety and Social Support in the Last Month of Pregnancy

Abstract: Background & Aim: Misconceptions and misinformation about childbirth can lead to cause mood symptoms such as anxiety and depression during pregnancy, which have irreversible effects on the developmental characteristics of birth, such as birth weight or Preterm delivery. The aim of this study was to determine the effect of preparation classes about physiological childbirth in the last month of pregnancy on depression, anxiety and social support. Methods: This study was semi-experimental. The statistical populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…32 Educating spouses during pregnancy reduces women's worry and anxiety. On the other hand, providing pregnancy training in the presence of spouses is an important factor in increasing women's social support 33,34 and improving couples’ relationships. 35 The results of a qualitative study showed that women refer to a healthy relationship with them and their husbands during pregnancy as one of the most important and effective factors in creating a positive pregnancy experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Educating spouses during pregnancy reduces women's worry and anxiety. On the other hand, providing pregnancy training in the presence of spouses is an important factor in increasing women's social support 33,34 and improving couples’ relationships. 35 The results of a qualitative study showed that women refer to a healthy relationship with them and their husbands during pregnancy as one of the most important and effective factors in creating a positive pregnancy experience.…”
Section: Discussionmentioning
confidence: 99%
“…Also, educating spouses during pregnancy leads to an increase in social support for women. 34 There is a significant relationship between social support and pregnancy experience so that with increasing the level of social support, pregnancy experience improves. 43 Women who are psychologically healthy during pregnancy see pregnancy as a manifestation of a sense of self-fulfillment and feminine identity, and also as a creative experience that leads to feelings of happiness.…”
Section: Discussionmentioning
confidence: 99%